Analysis of problem-solving skills: Impact of guided inquiry learning model based on Islamic values - Laila Puspita; K. Komarudin; Maya Astriani (University of Muhammadiyah Malang, 2020)
Islamic values have been recognized as the positive values need to be integrated in enhancing learning competencies including problem-solving skills. This study aimed to determine the influence of learning inquiry model based on Islamic values toward problem-solving skills of tenth-grade students in Bandar Lampung. This quasi-experimental research used posttest only control group design. The treatment for the experimental group used guided inquiry learning model based on Islamic values, whereas the direct instruction learning model was applied in control group. The students’ problem-solving skills data were collected using a test. The data was analyzed using independent samples t-test. The results showed that there was a significant influence of guided inquiry learning model based on Islamic values toward students’ problem-solving skills, t(58) = 2.807, p < .05. The integration of Islamic values in the biology learning process can promote students’ problem-solving skills. Therefore guided inquiry learning model based on Islamic values can be an alternative model in empowering students’ problem-solving skills.